Students’ Learning Style Preferences of English at Universitas Pamulang - Safitri, Hilma (TELL - US JOURNAL, 2016)
To have insight of the students learning style is vital since it can facilitate teacher to teach and decide what methods as well as activities are appropriate for the students, for instance,  in learning English. For the students in the future, it is hoped that they can recognize their own learning style preferences in order to be able to learn successfuly, because the students themselves may have no ideas of learning styles they prefer. They just imitate what their friends do, and the teacher does not understand what the students are like and what they prefer in learning. As the consequence, it will not result in any good effect for the improvement for their successful teaching and learning. Hence, both teacher and students, particularly the teachers need to know the students’ characteristics and their learning style preferances. This study adapted the Style Analysis Survey (SAS) model proposed by Oxford (1995) concerning the the student learning style preferences. The samples of this quantitative study involved 60 students who consisted of 30 of non-English and 30 English students at UNPAM. The data taken from quetionnaire were analyzed by using SPSS into descriptive statistic. It was found that the student learning style preferences of both non-English and English students mostly fell on the Social and affective. Meanwhile, for the individual learning style preferences of each group of students are  Physiological and Cognitive executive (II) in which non-English students will remember things better if they discuss them, and English students prefer realism instead of new, unstested ideas.